Predicting commitment in university students: the role of collective trust and self-efficacy - Shayo, Happy Joseph; Castulo, Nilo Jayoma; Oduro, Frederick; Marasigan, Arlyne C.; LY, Rambo; Aslam, Sarfraz (Frontiers in Psychology, 2025)
ObjectiveThis study tested whether collective trust in supervisors predicts university students’ affective commitment and whether student self-efficacy mediates this relationship. Demographic variables (age, sex, grade level, and major) were evaluated as potential moderators.MethodA cross-sectional, explanatory, non-experimental survey was administered to 968 students at a normal Chinese university. Measures included an adapted collective trust scale, an eight-item general self-efficacy scale, and an affective commitment subscale. Data screening confirmed univariate normality. A two-step covariance-based SEM procedure was conducted in AMOS 24: confirmatory factor analysis established a 17-item measurement model, and the structural model tested the direct and indirect paths. Composite scores were computed for descriptive analysis. Mediation was evaluated with bootstrap resampling (2000), and moderation tests used Hayes’s PROCESS macro for SPSS.ResultsThe final measurement model demonstrated an acceptable fit. SEM results indicated that collective trust positively predicted affective commitment and self-efficacy with moderate effect sizes, while self-efficacy positively predicted affective commitment (weak effect); together, these predictors accounted for approximately 49.8% of variance in affective commitment, indicating a strong effect. Bootstrap mediation revealed a significant indirect effect of collective trust on commitment through self-efficacy (partial mediation). Moderation analyses produced partial support: age and grade level moderated the self-efficacy → commitment link, academic major moderated the trust → self-efficacy link, and most other interactions were non-significant.ConclusionThe findings highlight the joint importance of group-level trust and individual efficacy for institutional attachment and suggest the value of cluster-sensitive interventions. Longitudinal and multi-site research is recommended to confirm causal pathways and boundary conditions.